ANALYSIS OF LITERARY RECEPTIONS OF THE NOVEL "NOT PASAR NIGHT" BY PRAMOEDYA ANANTA TOER (Karya Ilmiah Mahasiswa (KIMA), 2024)
The aim of this research is to explain the intrinsic elements of the novel Bukan Pasar Malam which consists of theme, setting, characters, plot, point of view and message, through readers' responses, as well as the values ​​contained in the novel. To anticipate differences in understanding between writers and readers, an approach is needed to find out readers' responses to a literary work, one of which is by conducting research on literary reception. This type of research uses a qualitative descriptive research method. This study describes and analyzes the data. Using content analysis method, literary reception approach. The results of the research based on the reception of readers of Indonesian Literature Study Program students at the Indonesian Muslim University are the themes in the novel Bukan Pasar Malam which presents post-independence criticism of Indonesia regarding endemic KKN activities (corruption, collusion and nepotism) . The plot in the novel Bukan Pasar Malam is before and flashback. The main character in the novel is the character Aku. The setting presented is so beautiful that one can imagine and feel the place and atmosphere being told. The message from the reader's response is to love our parents, toil is only a support to see the afterlife and what we reap based on what we sow, appreciate the teacher's services. The point of view of this novel is in the first person. The style of language in the novel Bukan Pasar Malam is easily understood by all readers, using standard language and metaphorical figures of speech and the values ​​contained in this novel are based on the responses of Indonesian Literature Students at the Indonesian Muslim University including religion values, social values, moral values. and cultural values.